Essential oils and capsaicin in the diet of Jersey cows at early lactation and their positive impact on anti-inflammatory, antioxidant and immunological responses - Leal K.W. (2024)
© The Author(s), under exclusive licence to Springer Nature B.V. 2024.The objective of this work was to determine whether the addition of phytogenic compounds based on essential oils (carvacrol, eugenol, cinnamaldehyde) and resinous pepper oil (capsaicin) to the diet of Jersey cows at the beginning of lactation affects anti-inflammatory, antioxidant and immunomodulatory responses, as well as whether there are effects of EO on blood metabolites, ruminal fermentation, digestibility and milk production and composition. Six primiparous cows (370.00 ± 17 kg body weight (BW); 13.02 kg dry matter intake (DMI); 21 days of lactation and average milk production of 20 ± 2 L per day) were allocated to crossed experimental design (2 × 2) with two experimental periods of 28 days and two treatments. Blood, milk and rumen fluid were collected and, at the end of each period, feed and feces samples were collected to evaluate the apparent digestibility of nutrients. The groups were control (CLT) without supplementation and treated (BEO) with the addition of 150 mg/kg of dry matter of the phytogenic to the concentrated portion of the diet. Cows in the BEO group had lower numbers of leukocytes (P ≤ 0.05) and lymphocytes (P ≤ 0.02), but total protein and globulin levels were higher on days 21 and 28 (P ≤ 0.01). In the BEO group, the levels of immunoglobulin A, immunoglobulin heavy chain and transferrin were higher (P ≤ 0.05). The levels of ceruloplasmin, haptoglobin and C-reactive protein were lower in the BEO group (P ≤ 0.05). Lipid peroxidation levels and protein carbonyl content were lower in the BEO group. The total antioxidant capacity (P ≤ 0.09) and the activity of glutathione S-transferase (P ≤ 0.03) and glutathione peroxidase (P ≤ 0.05) were higher in the BEO group. Cows in the BEO group had lower pH (P ≤ 0.05), acetic acid concentrations (P ≤ 0.01) and higher protozoa counts (P ≤ 0.01). Our results suggest that phytogenic supplementation has positive effects on the health of Jersey cows in early lactation, characterized by immunostimulant, antioxidant and anti-inflammatory effects.